An in-silico approach to find a peptidomimetic targeting extracellular domain of HER3 from a HER3 Nanobody. (June 2017) - Pourhashem, Z.; Mehrpouya, M.; Yardehnavi, N.; Eslamparast, A.; Kazemi-Lomedasht, F.
Graphical abstract: Schematic structure of a Heavy chain antibody and a Nanobody. The CDR3 region of Nanobody has peptidomimetic properties. Highlights: We propose that the complementarity determining region (CDR3) of HER3 Nanobody is large enough to effectively interact with HER3 antigen as well as with the full Nb. We used standard online servers to find a peptidomimetic derived from a HER3 Nb. The results demonstrate that the CDR3 of HER3 Nb might be applied by itself as a peptidomimetic drug instead of the entire Nb. The paper shows the feasibility of peptidomimetic obtainings such as HER3 peptidomimetic design using in silico analysis. Abstract: HER3 is an important therapeutic target in cancer treatments. HER3 Nanobodies (Nbs) are a novel class of antibodies with several competitive advantages over conventional antibodies. A peptidomimetic derived from these Nbs can be considered to be a small peptide mimicking some of the molecular recognition interactions of a natural peptide or protein in a three-dimensional (3D) space, with a receptor that has improved properties. In this study, we introduce a new approach to design a peptidomimetic derived from HER3 Nb through an in silico analysis. We propose that the complementarity determining region (CDR3) of HER3 Nb is large enough to effectively interact with HER3 antigen as well as with the entire Nb. A computational analysis has been performed using Nb models retrieved from SWISS-pdb Viewer 4.1.0 (spdbv) as a target spot and HER3 extracellular domain as its antigenic target to identify the interactions between them by the protein–protein docking method. Detailed analysis of selected models with docked complex help us to identify the interacting amino acid residues between the two molecules. The results of in silico analysis show that the CDR3 of HER3 Nb might be used by itself as a peptidomimetic drug instead of the full Nb. HER3 peptidomimetic-derived HER3 Nb may reduce Nb production costs and be used as a substitute for HER3 Nb after further experimental work. The paper demonstrates the feasibility of peptidomimetics designs using bioinformatic tools.